Retrobulbar Ocular Blood Flow Changes after Orbital Decompression in Graves' Ophthalmopathy Measured by Color Doppler Imaging - Pérez-López, Marta; Sales-Sanz, Marco; Rebolleda, Gema; Casas-Llera, Pilar; González-Gordaliza, Cristina; Jarrín, Elena; Muñoz-Negrete, Francisco José (Investigative ophthalmology & visual science, 2011)
To evaluate if decompression surgery produces changes in retrobulbar blood flow parameters in Graves' ophthalmopathy (GO). Retrobulbar blood vessels of 26 eyes (14 patients) that underwent orbital bone decompression between June 2009 and May 2010 were measured prospectively using color Doppler ultrasound before and after surgery. The disease was inactive in all patients enrolled according to the European Group on Graves' Orbitopathy. Patients were classified with mild, moderate-to-severe, or sight-threatening disease. All patients underwent a full ophthalmic examination including intraocular pressure and Hertel measurement. An age-matched control group included 20 eyes of 20 healthy volunteers. The resistance indexes (RIs) in the central retinal artery (CRA) and ophthalmic artery (OA) were significantly higher in patients with GO preoperatively than in the control group (P < 0.001, P = 0.001 respectively). After decompression surgery, a significant decrease in RIs occurred in the CRA (5%) and OA (6%) (P = 0.002, P < 0.001 respectively). Proptosis was decreased a median of 6 mm (range, 4-7). Three-wall decompression surgery resulted in a significantly greater reduction in exophthalmos (median 7 mm) compared with two-wall surgery (median 5 mm) and one-wall surgery (2.5 mm). Although no significant correlation was found, the RIs decreased more with major reductions in exophthalmos. In inactive moderate-to-severe GO, the RIs of the CRA and OA are higher than in normal subjects. The authors hypothesized that increased RIs of inactive GO may be due to orbital extrinsic compression of vascular structures because decompression surgery leads to decreases in the RIs of both the CRA and OA.